Analisis Peramalan Peluang Bisnis Tanah Menggunakan Metode Double Exponential Smoothing: (Studi Kasus: PT Jaya Nasional Famili pada Kota Malang) - Muhammad Haidar Hammam; Eka Larasati Amalia; Agung Nugroho Pramudhita (UPT P2M State Polytechnic of Malang, 2021)
PT. JNF is a company engaged in Engineering, Construction, and Project Management, located in South Jakarta. This company wants to develop its business by building housing in the city of Malang, to be precise in the Kedungkandang and Lowokwaru districts. The company needs some data and information about population density and land prices in the area to help the process of their project work. Providing information on data and forecasting results about population density and land prices in the area will help companies facilitate business development. Therefore, companies need an information system that can predict population density data and land prices in Kedungkandang sub-district and Lowokwaru sub-district, which functions to help companies see land business opportunities in Malang for housing development. The method used to make this system is the Double Exponential Smoothing method, because this method has a trend pattern that matches the data pattern of the object to be predicted. The data used are data from 2005 - 2018. The result of population density forecasting for Lowokwaru sub-district is 8713.98 and has a MAPE value of 1.39%, for Kedungkandang sub-district is 4949.07 and has a MAPE value of 2.55%, for the land price of Lowokwaru sub-district is 2777725.18 and has a MAPE value of 3.45 % and Kedungkandang sub-district is 1766560.27 and has a MAPE value of 8.36%. Based on the calculation of the MAPE value the results of the forecast above, it can be concluded that if the greater the constant value, the lower the MAPE value, the best constant value is between 0.6 - 0.9. The land business opportunity in Lowokwaru and Kedungkandang sub-districts is high based on the forecasting results of population density and land prices which tend to increase every year and the land business opportunity value based on ROI (Return of Investment) for the company is 0.38% of the initial capital. Keywords: information systems, forecasting, land business opportunities, land prices, population density, double exponential smoothing.